Perlidae from Brasil: reducing Linnean e Wallacean shorfalls - Almeida, Lucas Henrique de (2022)
The order Plecoptera is composed of aquatic insects that inhabit mainly low and medium-order lotic environments, which are also important indicators of environmental quality. Among the plecopterans, the Perlidae family has the largest number of known species (about 30%) and is also the most diverse in the Neotropical Region and in Brazil. In Brazil, the family is represented by the genera Anacroneuria, Enderleina, Kempnyia, and Macrogynoplax. Despite recent advances in the study of Brazilian perlids, shortfalls in knowledge about diversity remain present. In this study, we studied the Brazilian fauna of Perlidae (Plecoptera) in order to reduce biodiversity shortfalls, especially the Linnean (lack of knowledge about existing species) and Wallacean shortfalls (lack of knowledge about the geographic distribution of species). Here, we describe six new species of Perlidae: Anacroneuria duarte sp. nov., A. sallesi sp. nov., Enderleina castro sp. nov., Kempnyia guarani sp. nov., K. tupiniquim sp. nov., and K. zwicki sp. nov. We proposed the synonymy of Kempnyia sordida with K. obtusa, we recorded for the first time Anacroneuria pakitza and Macrogynoplax yupanqui in Brazil, we performed several new records in different states, and we count several new occurrence points for dozens of species. In addition, we organized all the existing taxonomic knowledge about Perlidae from Brazil, generating a list with information on described semaphoronts and scientific articles that cited the 152 known species. Through the compiled occurrence data, we were able to discuss the sampling effort carried out from a political and phytogeographic perspective, highlighting the need to continue to expand the sampled locations. We also discussed the difficulties faced by the taxonomy of Perlidae from Brazil, highlighting the presence of problematic species, the difficult species delimitation, impediments in the association of nymphs, and the few phylogenetic, biogeographic, and ecological studies. We conclude by presenting the perspectives of future studies on Brazilian perlids.